The labor market costs of work-related stress: A longitudinal study of 52 763 Danish employees using multi-state modeling - Jacob Pedersen; Brian Krogh Graversen; Kristian Schultz Hansen; Ida Elisabeth Huitfeldt Madsen (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVE: Work-related stress is an important public health concern in all industrialized countries and is linked to reduced labor market affiliation and an increased disease burden. We aimed to quantify the labor market costs of work-related stress for a large sample of Danish employees. METHODS: We linked four consecutive survey waves on occupational health and five national longitudinal registers with date-based information on wage and social benefits payments. From 2012 to 2020, we followed survey participants for two year-periods, yielding 110 559 person-years. We identified work stress by combining three dichotomous stress indicators: (i) self-perceived work stress, (ii) Cohen 4-level perceived stress scale, and (iii) job strain. Using the multi-state expected labor market affiliation (ELMA) method, we estimated the labor market expenses associated with work-related stress. RESULTS: Of the employees, 26-37% had at least one work-stress indicator. Men aged 35-64 years and women aged 18-64 years with work-related stress had up to 81.6 fewer workdays and up to 50.7 more days of sickness absence during follow-up than similarly aged men without work stress. The average annual work absenteeism loss per employee linked to work-related stress was €1903 for men and €3909 for women, corresponding to 3.3% of men's average annual wages and 9.0% of women's average annual wages, respectively. The total annual expenses were €305.2 million for men and €868.5 million for women. CONCLUSION: Work-related stress was associated with significant labor market costs due to increased sickness absence and unemployment. The prevention of work-related stress is an important occupational health concern, and the development of effective interventions should be given high priority.